TRILOGI PEMBEBASAN ASGHAR ALI ENGINEER: Tafsir Anti Kemapanan atas Ketidakadilan - Riady, Fahmi (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
The liberation theology is a theology which puts great ernphasis on fieedom, equality and distributive justice and strongly condemns exploitation of rnan by man, opprcssion and pcrsccution. lhe main character olthis thcology is its conccrn to thc mustadhafun (the weak people). Suclr tlrc ology didnt want the status quo rvhich protect the rich people. Its anti-status quo either in religoLrs field or politic one. Such theology play the imporlant role in caring tbr the weak people who his right was under attack. Its also give thc weak a strong ideological weapon facing its tyrant. ln l